2019
DOI: 10.1177/1753425918820427
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells are bound and inhibited by anti-thymocyte globulin

Abstract: Myeloid-derived suppressor cells (MDSCs) inhibit T cell responses and are relevant to cancer, autoimmunity and transplant biology. Anti-thymocyte globulin (ATG) is a commonly used T cell depletion agent, yet the effect of ATG on MDSCs has not been investigated. MDSCs were generated in Lewis Lung Carcinoma 1 tumor-bearing mice. MDSC development and function were assessed in vivo and in vitro with and without ATG administration. T cell suppression assays, RT-PCR, flow cytometry and arginase activity assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Animal studies have shown that adoptive transfer of MDSCs can prolong survival of islets, skin, as well as cardiac allografts 4,5,36‐38 ; but little more is known about the ability of MDSCs to control graft survival. Our group recently showed that anti‐thymocyte globulin affects MDSC expansion and survival, suggesting that common transplant drugs may alter the immunosuppressive capacities of MDSCs 3 . Here, we showed that in the absence of immunomodulatory drugs, MDSCs were expanded after transplantation.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Animal studies have shown that adoptive transfer of MDSCs can prolong survival of islets, skin, as well as cardiac allografts 4,5,36‐38 ; but little more is known about the ability of MDSCs to control graft survival. Our group recently showed that anti‐thymocyte globulin affects MDSC expansion and survival, suggesting that common transplant drugs may alter the immunosuppressive capacities of MDSCs 3 . Here, we showed that in the absence of immunomodulatory drugs, MDSCs were expanded after transplantation.…”
Section: Discussionmentioning
confidence: 67%
“…Human studies showed that MDSCs expand in peripheral blood after kidney transplantation 9,13 . However, immunosuppressive drugs markedly affect MDSC expansion 3,11,22 . We sought to determine if the inflammatory milieu of transplantation alone could induce recipient MDSC expansion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations